Positive youth development: the role of the youth-adult partnership and hardiness - Nouri, Katayoun M.; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This article explores the relevant literature on youth-adult partnership and hardiness as important contributors to positive youth development. Despite a rich literature on the importance of youth-adult partnership in achieving positive youth development outcomes, the mechanisms through which this takes place are not yet fully understood, especially in non-Western cultural contexts. This study aims to extend this work by proposing the role of hardiness that is an interacting set of positive attitudes in youth as a potential moderator of relationships between youth-adult partnership and positive youth development. Hardiness has been shown to be an important contributor to positive youth development outcomes. This article depicts positive youth development as a practice in which youths play a central role in their own development. Specifically, the discussion centres on how youth-adult partnership, which is the relationships between youth and adults in community settings, can enhance the positive development of youths and how hardiness may play a role as a moderator in this relationships. This achieved by two main components of youth-adult partnership, which are youth voice in decision making and supportive adult relationships. Although much of the current debate revolves around youth-adult partnership affecting positive outcomes of youth, there are ambiguities in this area. This article is an attempt to address the gap in knowledge concerning the relationship between youth-adult partnership and positive youth development. More so, to date there has been a lack of research into the role of hardiness in promoting positive youth development. Thus, to portray the issue in terms of hardiness, this paper attempts to clarify hardiness as a moderator in this relationship. In conclusion, evidence suggests a strong relationship between youth-adult partnership and positive youth development outcomes, and the potential of hardiness to further enhance this relationship. Therefore, more empirical work is needed to test this relationship.